Estimation of total bacteria by real-time PCR in patients with periodontal disease - Brajović Gavrilo; Popović Branka; Puletić Miljan; Kostić Marija; Milašin Jelena (Srpski Arhiv za Celokupno Lekarstvo, 2016)
Introduction. Periodontal diseases are associated with the presence of elevated levels of bacteria within the gingival crevice. Objective. The aim of this study was to evaluate a total amount of bacteria in subgingival plaque samples in patients with a periodontal disease. Methods. A quantitative evaluation of total bacteria amount using quantitative real-time polymerase chain reaction (qRT-PCR) was performed on 20 samples of patients with ulceronecrotic periodontitis and on 10 samples of healthy subjects. The estimation of total bacterial amount was based on gene copy number for 16S rRNA that was determined by comparing to Ct values / gene copy number of the standard curve. Results. A statistically significant difference between average gene copy number of total bacteria in periodontal patients (2.55.107) and healthy control (2.37.106) was found (p=0.01). Also, a trend of higher numbers of the gene copy in deeper periodontal lesions (>7 mm) was confirmed by a positive value of coefficient of correlation (r=0.073). Conclusion. The quantitative estimation of total bacteria based on gene copy number could be an important additional tool in diagnosing periodontitis. [Projekat Ministarstva nauke Republike Srbije, br. 175075]